2019
DOI: 10.1088/1757-899x/688/4/044024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lane Reduction “Road Diet” Measures in China

Abstract: Road diet measures are widely used abroad, but they have not been implemented in China. One of the important reasons is that we usually think that the reduction of the number of lanes will cause traffic congestion. In order to evaluate the impact of lane reduction “road diet”measures, we implemented road diet reform measures in Shoushan Road to Longxing Road section of Xinghai North Street, Xingcheng City. After nearly one year of adaptation, we evaluate the implementation plan from three aspects in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that a road diet increases cyclists and reduces motor vehicle speed (Gudz et al, 2016). A study in China also showed that the road diet increases the number of cyclists and makes it easier for pedestrians to cross (Huang et al, 2019). Reducing the number of motorized vehicle lanes, reducing motor vehicle access, and reducing on-street parking will make an area walkable (Knapskog et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a road diet increases cyclists and reduces motor vehicle speed (Gudz et al, 2016). A study in China also showed that the road diet increases the number of cyclists and makes it easier for pedestrians to cross (Huang et al, 2019). Reducing the number of motorized vehicle lanes, reducing motor vehicle access, and reducing on-street parking will make an area walkable (Knapskog et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We do not review the literature on the effect of active travel facilities on motorist volumes here. But there is evidence that active travel improvements like road diets (Gudz, Fang, & Handy, 2016;Huang, Stewart, & Zegeer, 2002) and complete streets retrofits (Shu, Quiros, Wang, & Zhu, 2014) can increase bicycling or pedestrian volumes while having little to no effect on vehicular traffic flow. In addition, a recent review of the literature on changes in bicycle ridership following installation of a new bicycle facility concluded that "sizeable percentage increases in ridership can be expected along the routes of new Class I, Class II, and Class IV facilities" (Volker et al, 2019a, p. 20;Volker & Handy, 2019).…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%